2022
DOI: 10.1016/j.rmcr.2021.101559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benralizumab in a patient with uncontrolled severe eosinophilic asthma and comorbid chronic rhinosinusitis with nasal polyps refractory to mepolizumab treatment

Abstract: Severe eosinophilic asthma is associated with a high corticosteroid burden, particularly in patients with comorbid chronic sinusitis/nasal polyps. This case study reports a 33-year-old woman who presented to the severe asthma center with uncontrolled severe eosinophilic asthma and chronic rhinosinusitis with nasal polyps (CRSwNP). Despite maximized asthma treatment, including maintenance oral corticosteroids (OCS) for 7 years, the patient experienced one to two hospitalizations per year, had daily symptoms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…Finally, we analysed the subgroup of patients with SEA and CRSwNP, and although no differences were detected within the SNOT-22 score and number of recurrences, we confirmed that benralizumab treatment resulted in a marked improvement in asthma control, suppressed blood eosinophil levels and reduction in the number of exacerbations. Similar findings are reported in a recent case report of Mansur AH [ 23 ]. Another interesting finding observed is the reduction in FeNO; even literature data are still unclear on this.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we analysed the subgroup of patients with SEA and CRSwNP, and although no differences were detected within the SNOT-22 score and number of recurrences, we confirmed that benralizumab treatment resulted in a marked improvement in asthma control, suppressed blood eosinophil levels and reduction in the number of exacerbations. Similar findings are reported in a recent case report of Mansur AH [ 23 ]. Another interesting finding observed is the reduction in FeNO; even literature data are still unclear on this.…”
Section: Discussionsupporting
confidence: 92%
“…[5] This case report demonstrated the efficacy of bendralizumab treatment in a patient with uncontrolled severe eosinophilic asthma refractory to omalizumab treatment and another study conducted by Adel H. Mansur et al reported the efficacy of bendralizumab treatment in a patient with severe eosinophilic asthma and chronic rhinosinusitis with nasal polyps refractory to mepolizumab treatment. [3] In the present study, treatment of uncontrolled severe eosinophilic asthma with bendralizumab appears to be feasible, rapid and safe. A study conducted by Andrea baccelli et al reported that mepolizumab may be beneficial and safe as an add-on biologic in a patient with uncontrolled severe eosinophilic asthma.…”
Section: Discussionmentioning
confidence: 67%
“…[2] Severe asthma is associated with frequent exacerbations that lead to the excessive use of systemic corticosteroids (SCS) that, with their associated side effects, can be burdensome to the lives of patients. [3] For patients with severe refractory asthma, monoclonal antibodies are a relatively novel therapeutic option that can be added to maintenance therapy. This reduces the requirement for systemic corticosteroid use, improves asthma symptom control, and lowers exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…Switching biologicals is an option when adverse reactions are encountered or when response is suboptimal. The literature on switching biologicals in CRSwNP is currently in the form of a few case reports, 51,52 although we may draw from the experience of switching biologicals in asthma. A historical cohort study of over 3500 patients with severe asthma from 11 countries found that the overall rate of discontinuing or switching biologicals was low, at about 10% 53 .…”
Section: Incorporating Biologicals Into Crswnp Treatmentmentioning
confidence: 99%